Banks' earnings, risks and returns in China - Cheng, Fan Fah; Md Nasir, Annuar (David Publishing, 2011)
This study aims to find the effect of financial risks, price risks and market risks on the Earning Response Coefficients (ERC) for China Commercial Banks. The research methodologies use the traditional cumulative abnormal returns and the unexpected earning as the main dependent and independent variables. The evidences show that: (1) There is a strong returns-to-earnings relation for banks; (2) The liquidity risk has information content beyond earnings changes in the returns-to-earnings relation. This probably due to the reason that managers of banks find the level of liquidity that fulfilled the need of investors and at the same time earns good profits for the banks.